Inhibition of Advanced Glycation End Products in Yogurt by Lotus Seedpod Oligomeric Procyanidin - Feng, Nianjie; Shen, Yang; Hu, Chuanqin; Tan, Jiangying; Huang, Zhao; Wang, Chao; Guo, Zhiqiang; Wu, Qian; Xiao, Juan (Frontiers in Nutrition, 2021)
The basic ingredients of yogurt include lactose and protein. Yogurt undergoes the Maillard reaction easily, producing many advanced glycation end products (AGEs) that cause some chronic diseases. Lotus seedpod oligomeric procyanidin (LSOPC) have demonstrated a strong inhibitory effect on AGE formation in simulated models; however, the inhibition of procyanidin on AGE formation and the subsequent effects on yogurt quality remains unknown. Our study demonstrated that LSOPC had a good inhibitory effect on the formation of fluorescent AGEs and Nε-carboxymethyl lysine (P < 0.05). The inhibitory capacity on AGEs and antioxidant activity of yogurt were positively correlated with the concentration of LSOPC. The effect of LSOPC on the physicochemical properties of yogurt was also evaluated. Bound water content, viscosity, and flavor of yogurt were significantly increased after LSOPC addition (P < 0.05). Therefore, LSOPC may lead to significant benefits for controlling AGE formation and improving the quality of yogurt.